2013
DOI: 10.1007/978-3-642-42033-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scene of Side Channel Attacks

Abstract: Abstract. Since the introduction of side channel attacks in the nineties, a large amount of work has been devoted to their effectiveness and efficiency improvements. On the one side, general results and conclusions are drawn in theoretical frameworks, but the latter ones are often set in a too ideal context to capture the full complexity of an attack performed in real conditions. On the other side, practical improvements are proposed for specific contexts but the big picture is often put aside, which makes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…a far-away bump in the trace not related to k can affect the leakage samples that matter most. Another possibility, to deal with the lowfrequency offset, might be to use electromagnetic leakage, as this leakage is not affected by low-frequency components, so it may provide better results [16].…”
Section: Compensating For the Offsetmentioning
confidence: 99%
See 1 more Smart Citation
“…a far-away bump in the trace not related to k can affect the leakage samples that matter most. Another possibility, to deal with the lowfrequency offset, might be to use electromagnetic leakage, as this leakage is not affected by low-frequency components, so it may provide better results [16].…”
Section: Compensating For the Offsetmentioning
confidence: 99%
“…However, most previous studies [2,5,8,10,17] used the same device (and possibly acquisition campaign) for the profiling and attack phases. Only recently, Renauld et al [12] performed an extensive study on 20 different devices, showing that the template attack may not work at all when the profiling and attack steps are performed on different devices; Elaabid et al [14] showed that acquisition campaigns on the same device, but conducted at different times, also lead to worse template-attack results; and Lomné et al [16] evaluated this scenario using electromagnetic leakage.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be noted that NICV is considered as the relevant distinguisher for the Linear Regression Analysis (LRA) [19,22], which acts as the CPA but with a parametric leakage model. Now, if X is uniformly distributed, the NICV in itself is not a distinguisher.…”
Section: Rationale Of the Nicv Detection Techniquementioning
confidence: 99%
“…in [2]), Pearson's ρ has been used in almost all correlation power attacks over the last decade, since it allows for an efficient correlation computation. The work performed in [16] also investigates reducing the algorithmic complexity of various power analysis attacks. In the extended version of this work CPA is considered as well [17].…”
Section: Introductionmentioning
confidence: 99%
“…The work performed in [16] also investigates reducing the algorithmic complexity of various power analysis attacks. In the extended version of this work CPA is considered as well [17]. However, the focus is on partitioning the traces and computing statistical information on these smaller partitions (in the setting of CPA using the ideas from [15]) while this paper also tries to look into computational aspects when the number of traces and samples is fixed.…”
Section: Introductionmentioning
confidence: 99%